(untitled) (Revista de História Regional, 2007)
The objective of this article is to discuss the constitution of the working class of Uberabinha/MG in the period from 1888 to 1915 starting from the exam of the experiences of freed slaves work and of immigrants. I try initially to identify and to examine the manners of living of those two groups of workers investigating on their organization strategies and of resistance for, soon afterwards, to evaluate to what extent they formed a common perception on the world in that they lived. The points considered central for that analysis they are the work that each one of those groups exercised, the action of the State on them and, in some measured, the vision that they had on themselves.